Preparation, Characterization, and Antioxidant Features of Some New Schiff Bases Derived from Isatins and Hydrazine - MUĞLU, Halit; YAKAN, Hasan (Igdir University, 2020)
New isatins based on Schiff bases were prepared from hydrazine, 5-substituted isatins, and aldehydes under reflux in ethanol. The structures of the synthesized compounds were elucidated by using IR, 13C NMR, 1H NMR spectroscopy and elemental analysis. All the compounds were tested in vitro antioxidant activity with free radical scavenging method using by 1,1-diphenyl-2-picryl hydrazyl (DPPH). The results were given with calculated IC50 values.
Keywords: Schiff bases; isatin; antioxidant features; spectroscopic method; DPPH; Chemical Engineering; Schiff baz; isatin; antioxidant özellikler; spektoskopik yöntem; DPPH; Kimya Mühendisliği